T cells specific to multiple Bet v 1 peptides are highly cross-reactive toward the corresponding peptides from the homologous group of tree pollens - Lund, Gitte; Christensen, Lars Harder; Ihlemann, Jacob; Andersen, Peter Sejer; Wambre, Erik; Würtzen, Peter Adler; Gupta, Shashank (Frontiers in Immunology, 2023)
Background: Allergens from Fagales trees frequently cause spring allergy in Europe, North America, and some parts of Asia. The definition of the birch homologous group, which includes birch (Bet v), oak (Que a), alder (Aln g), hazel (Cor a), hornbeam (Car b), beech (Fag s) and chestnut (Cas s) is based on high allergen sequence identity and extensive IgE cross-reactivity. Clinical effect was seen during the alder/hazel, birch, and oak pollen seasons after treatment with tree SLIT-tablets containing only birch allergen extract. Here, we characterise T-cell reactivity with respect to epitope specificities and cross-reactivity toward various Bet v 1 family member, PR-10 / group 1 major allergens. This cross-reactivity may be part of the to further investigate the immunological basis of clinical effect or cross-protection when exposed to birch homologous tree speciescross-protection. Method: T-cell lines were generated from 29 birch allergic individuals through stimulation of PBMC with birch/Bet v or oak/Que a allergen extracts. T-cell responses to allergen extracts, purified group 1 allergens, and overlapping 20-mer peptides (Bet v 1, Aln g 1, Cor a 1, Que a 1) were investigated by T-cell proliferation and cytokine production. Cross-reactivity was evaluated based on Pearson correlations of response strength and further investigated by FACS flow cytometry using tetramer staining for homologous peptide pairs. Results: T-cell reactivity toward extracts and group 1 allergens from across the birch homologous group was observed for birch/Bet v as well as oak/Que a T-cell lines. T-cell lines responded to multiple Bet v 1 homologous peptides from Aln g 1 and Cor a 1 and a subset of Que a 1 peptides. Significant Pearson correlations between frequently recognized peptides derived from Bet v 1 and the corresponding peptides derived from alder, hazel, and oak strongly supported the T-cell cross-reactivity towards these allergens. Cross-reactivity between birch and birch homologous peptides was confirmed by pMHCII-tetramer staining. Conclusion:T-cells from birch tree pollen allergic individuals respond to multiple trees within the birch homologous group in accordance with the level of sequence homology between Bet v 1 family member, PR-10 group 1 allergens from these allergen sources confirming the basis for clinical cross-protection.